Mental files and metafictive utterances - Lo Guercio, Nicolás Francisco (2015)
Metafictive utterances raise a kind of intuitions (intuitions of truthfulness) that pose a problem for a view that combines a referentialist approach to proper names with an antirealist stance on fictional characters. In this article I attempt to provide a solution to this problem within the framework of mental files. According to my position, metafictive utterances literally express an incomplete proposition while pragmatically conveying a complete one, which accounts for the intuitions of truthfulness. The proposition pragmatically conveyed is 'metarepresentational', I'll argue, in the sense that it is about a mental representation or mental file.